Epinephrine use in older patients with anaphylaxis: Clinical outcomes and cardiovascular complications. (March 2017) - Kawano, Takahisa; Scheuermeyer, Frank Xavier; Stenstrom, Robert; Rowe, Brian H.; Grafstein, Eric; Grunau, Brian
Abstract: Background: There is little data describing the differences in epinephrine (epi) administration and cardiac complications among older and younger patients with anaphylaxis. Methods: This retrospective cohort study was conducted at two urban emergency departments (ED) over a 5 year-period, and included adults who met a pre-specified criteria for anaphylaxis. Patients ≥50 years of age were defined as "older". Univariate logistic regression was performed to compare the difference in frequency of epi administration between the "older" and "younger" groups. Among those who received epi, the proportion of patients who received doses exceeding the recommended maximum and who had pre-specified cardiovascular complications were compared between the two groups, stratified further by route of administration. Results: Of 2995 allergy-related visits, 492 met criteria for anaphylaxis, including 122 (24.8%) older patients. Older patients were less likely to receive epi injection (36.1% vs. 60.5%). Of those who received epi, older patients were more likely to receive excessive dose of epi (7/44, 15.9% vs 2/225, 0.9%, unadjusted OR 20.7, 95% CI 3.8–211.7). Four (4/44, 9.1%) older patients experienced cardiovascular complications, compared to 1/225 (0.4%) in the younger group (unadjusted OR 22.4, 95% CI 2.1–1129.8). When examining only intra-muscular epinephrine, 1/31 older patients had cardiac complications, compared to 1/186 in the younger group. Conclusion: Older patients with anaphylaxis were less likely to receive epi injection. Intramuscular epi appears safe in this population; however, the use of intravenous epi should be avoided in older patients due to the potential of developing serious cardiac complications.